Heterogeneity in ‘High Fertility’ Societies. Insights From Compositional Demography - Bras, Hilde (Historical Life Course Studies, 2021)
Demographic transition theory has been conducive to a rather dichotomous view of global fertility: traditional versus modern, high versus low fertility. The knowledge that high fertility could be achieved by subpopulations with different characteristics and reproductive behaviors somehow vanished from (historical) demographers’ attention. This study unpacks heterogeneity in a ’high fertility’ society, i.e. 19th-century Zeeland, the Netherlands. Sequence and cluster analysis were employed to distinguish groups with disparate reproductive trajectories with data from Genlias/LINKS including 15,014 full birth histories and 87,204 observed live births over the period 1811–1911. Multilevel binomial logistic regression models of membership of the two discerned high fertility subgroups were then estimated. The ’Traditional 1’ subpopulation, with 10.5 children per woman on average, was composed of skilled, unskilled, and farm workers living in rural areas. Couples married early and were characterized by large spousal age gaps. The ’Traditional 2’ subpopulation had on average 7.2 children per woman, more often lived in towns, married significantly later, and had more equal gender relations. Compositional demography, revealing subpopulations with divergent cultures of marital self-restraint and reproductive management, not only nuances previous (historical) demographic findings, but may well offer more tools to develop family planning and reproductive health policies than the demographic transition model does.